An intercalated UV absorbing product and a production method thereof - Hussein, Mohd. Zobir; Megat Nabil Mohsin, Sumaiyah; Sarijo, Siti Halimah; Fakurazi, Sharida; Arulselvan, Palanisamy (2013)
The present invention relates to ultraviolet (UV) absorbers-intercalated layered double hydroxide (LDH) product. The present invention also provides a simple and energy efficient co-precipitation method for simultaneous intercalation of two UV absorbers into layered double hydroxide (LDH).